Molecular prioritization strategies to identify functional genetic variants in the cardiovascular disease-associated expression QTL Vanin-1 - Kaskow, B.; Diepeveen, L.; Michael Proffitt, J.; Rea, A.; Ulgiati, D.; Blangero, J.; Moses, Eric; Abraham, L. (2014)
There is now good evidence that non-coding sequence variants are involved in the heritability of many common complex traits. The current 'gold standard' approach for assessing functionality is the in vitro reporter gene assay to assess allelic differences in transcriptional activity, usually followed by electrophoretic mobility shift assays to assess allelic differences in transcription factor binding. Although widely used, these assays have inherent limitations, including the lack of endogenous chromatin context. Here we present a more contemporary approach to assessing functionality of non-coding sequence variation within the Vanin-1 (VNN1) promoter. By combining 'gold standard' assays with in vivo assessments of chromatin accessibility, we greatly increase our confidence in the statistically assigned functional relevance. The standard assays revealed the-137 single nucleotide variant to be functional but the-587 variant to have no functional relevance. However, our in vivo tests show an allelic difference in chromatin accessibility surrounding the-587 variant supporting strong functional potential at both sites. Our approach advances the identification of functional variants by providing strong in vivo biological evidence for function.